A mathematics for medicine: The Network Effect - West, Bruce J. (Frontiers in Physiology, 2014)
The theory of medicine and its compliment systems biology are intended to explain the workings of the large number of mutually interdependent complex physiologic networks in the human body, and to apply that understanding to maintaining the functions for which nature designed them. Therefore, when what had originally been made as a simplifying assumption or a working hypothesis becomes foundational to understanding the operation of physiologic networks, it is in the best interests of science to replace or at least update that assumption. The replacement process requires, among other things, an evaluation of how the new hypothesis affects modern day understanding of medical science. This paper identifies linear dynamics and Normal statistics as being such arcane assumptions and explores some implications of their retirement. Specifically, we explore replacing Normal with fractal statistics, and examine how the latter are related to nonlinear dynamics and chaos theory. The observed ubiquity of inverse power laws in physiology entails the need for a new calculus, one that describes the dynamics of fractional phenomena and captures the fractal properties of the statistics of physiological time series. We identify these properties as a necessary consequence of the complexity resulting from the network dynamics, and refer to them collectively as The Network Effect.